CrN coatings deposited by magnetron sputtering: mechanical and tribological properties (2015)
Mechanical and tribological properties of CrN coatings grown on steel substrates AISI 304 and AISI 4140 using the magnetron sputtering technique were analyzed. Coatings were grown at two pressures of work, 0.4 and 4.0 Pa. The films grown on AISI 304 at a pressure of work of 0.4 showed the highest hardness because it presented a larger grain size and lower roughness. For CrN synthesized at 0.4 Pa, the surface damage was lower during the tribological test. Adherence studies were also carried out, obtaining Lc1 and Lc2 for coatings produced at both pressures and on both substrates. Better adherence behavior was observed for films grown at a low pressure because these films were thicker (~890 nm).